Radiolabeling of porcine, murine growth hormone and a potential antagonist G118R-mGH for biodistribution study - Amanda Palermo Nunes; Filipe Menezes; Larissa Andrade Almeida; Stephanie A. Pomin; Patricia Lima Falcão; Carlos Soares (Brazilian Journal of Radiation Sciences, 2025)
This study aimed to radiolabel porcine growth hormone (pGH), murine growth hormone (mGH), and its antagonist (G118R-mGH) with the iodine radioisotopes ¹³¹I and ¹²³I, to investigate the biodistribution and brain transport of these hormones. Radiolabeling was performed using the Chloramine T method, a protein iodination technique. The radiolabeled products were characterized by physicochemical techniques such as SDS-PAGE, size-exclusion high-performance liquid chromatography (HPLC-SE), and ascending paper chromatography, with measurements performed using single-photon emission computed tomography (SPECT).  These measurements demonstrated high radiochemical purity, exceeding 95%, and preservation of molecular size. In vitro stability assays indicated that the radiotracers maintained their integrity for at least 24 hours. In vivo biodistribution studies in mice revealed distinct tissue distribution patterns for mGH and G118R-mGH, suggesting different uptake and metabolism mechanisms. The use of ¹²³I allowed for SPECT-CT imaging studies, which proved important for assessing the ability of mGH and G118R-mGH to cross the blood-brain barrier and distribute in specific regions of the brain. The results obtained in this work highlight the versatility of the radiolabeling protocol employed and its potential for investigating complex biological processes and application in research.